ANALISIS INTERAKSI SOSIAL REMAJA BROKEN HOME DI RT 009/RW 002 KRAJAN TENGARAN - Ramandani, Indri Ashari; Tagela, Umbu; Irawan, Sapto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was conducted to study how adolescents with broken home family backgrounds interact socially. The research method used was qualitative research. Data were collected through interview and observation techniques on broken home adolescents in RT 009/RW 002 Krajan Tengaran. The results showed that, 1) Social interaction of adolescents between individuals with individuals is not good, the three adolescents tend to the three adolescents tend to hide their own problems, do not like to hang out with many friends and limit themselves with others. The three adolescents also showed selfishness in interacting. What became the factors for this are divorce, separation of parents and no harmonious relationship between family members. 2) Social interaction of broken home adolescents with groups, the three adolescents were more quiet, aloof and did not like to hang out with friends in the group they participated in. Of the three adolescents also showed a high level of emotional sensitivity, making them vulnerable to taking offense in interactions with the surrounding environment.